Analisis kelayakan modul fisika berbasis kontruktivis dalam pembelajaran inkuiri pada materi pelajaran fluida untuk meningkatkan hasil belajar siswa kelas XI SMA - Yulfia Syafri Yanti; Hufri Hufri (PILLAR OF PHYSICS EDUCATION, 2020)
Based on the 2019’s UNBK value in indonesia, the physics value obtained for west sumatera is 47.5, that cualified as relatively low. And the result of the analysis of two physics textbook in senior high school in Padang city  using the inquiry indicator instrument is 47% wich can be categoried as low.  So, those textbook haven’t facilitated the learning inquiry. One solution can be done by making a constructivist-based physics modules in inquiry learning. This study purposed to determine thw validity and practicality of constructivist-based physics modules in inquiry learning on the subject matter of XI senior high school classes.This reasearch type is R&D (Research and Development) by Sugiyono in consisting 10 steps. R&D research steps include potential and problems, data collection, products design, product validation, product revisions, product trials, and product revisions. This research limited to product revisions after product trials (practicality). Tests conducted to see the feasability of the modules that have been designed that is validity and practicality tests. Validity test was conducted by 3 experts (validators) who did the assesments of the six components of the validation of the module that have been designed.The practicality test was by physics teachers (3 peoples) and students of class xi IPA in Padang city Senior High School (15 peoples).The validity test consists of six components, namely the content feasibility test, the construction feasibility, the feasability of inquiry, the feasability of the language, the appearance of the module, and feasability of the constructivist, with an overall average of 82% in the very valid category. Practicality test obtained from the teachers response to the six practical indicators, namely the contents of the module, the performance of the module, the convenience of the module, benefit of the module, the presentation of the inquiry components and the construvtivist componen with an overall average of 81% in the very practical category. Whereas students responses to the six indicators of practicality with an overall average of 85% which categorized as very practical. So, constructivist-based physics modules in inquiry learning are in the very valid and very practical categories so they can be used in the learning process.